Neuropathy-causing mutations in HSPB1 impair autophagy by disturbing the formation of SQSTM1/p62 bodies. Issue 6 (3rd June 2019) - Haidar, Mansour; Asselbergh, Bob; Adriaenssens, Elias; De Winter, Vicky; Timmermans, Jean-Pierre; Auer-Grumbach, Michaela; Juneja, Manisha; Timmerman, Vincent
ABSTRACT: HSPB1 (heat shock protein family B [small] member 1) is a ubiquitously expressed molecular chaperone. Most mutations in HSPB1 cause axonal Charcot-Marie-Tooth neuropathy and/or distal hereditary motor neuropathy. In this study we show that mutations in HSPB1 lead to impairment of macroautophagic/autophagic flux. In HSPB1 knockout cells, we demonstrate that HSPB1 is necessary for autophagosome formation, which was rescued upon re-expression of HSPB1. Employing a label-free LC-MS/MS analysis on the various HSPB1 variants (wild type and mutants), we identified autophagy-specific interactors. We reveal that the wild-type HSPB1 protein binds to the autophagy receptor SQSTM1/p62 and that the PB1 domain of SQSTM1 is essential for this interaction. Mutations in HSPB1 lead to a decrease in the formation of SQSTM1/p62 bodies, and subsequent impairment of phagophore formation, suggesting a regulatory role for HSPB1 in autophagy via interaction with SQSTM1. Remarkably, autophagy deficits could also be confirmed in patient-derived motor neurons thereby indicating that the impairment of autophagy might be one of the pathomechanisms by which mutations in HSPB1 lead to peripheral neuropathy. Abbreviations: ACD: alpha-crystallin domain; ALS: amyotrophic lateral sclerosis; ATG14: autophagy related 14; BAG1/3: BCL2 associated athanogene 1/3; CMT: Charcot-Marie-Tooth; dHMN: distal hereditary motor neuropathy; GFP: green fluorescent protein; HSPA8: heat shock protein family A (Hsp70) member 8; HSPB1/6/8: heat shock protein family B (small) member 1/6/8; LIR: LC3-interacting region; LC3B: microtubule associated protein 1 light chain 3 beta; PB1: Phox and Bem1; SQSTM1: sequestosome 1; STUB1/CHIP: STIP1 homology and U-box containing protein 1; UBA: ubiquitin-associated; WIPI1: WD repeat domain, phosphoinositide interacting 1; WT: wild-type